Obesity and Physical Activity in the Daily Life of Patients with COPD - Monteiro, Fabiane; Camillo, Carlos Augusto [UNESP]; Vitorasso, Renato; Sant'Anna, Thais; Hernandes, Nidia A.; Probst, Vanessa S.; Pitta, Fabio (Springer, 2012)
The aim of this study was to investigate the differences in body composition between physically active and inactive patients with chronic obstructive pulmonary disease (COPD) and the relationship of obesity [according to body mass index (BMI) and percentage of fat mass (%FM)] with physical activity in the daily life (PADL) in this population.Body composition (bioelectrical impedance analysis) and level of PADL (activity monitors DynaPort and SenseWear) were evaluated in 74 patients with COPD (45 men, 65 +/- A 9 years old, FEV1 = 40 +/- A 15%pred, BMI = 27 +/- A 6 kg m(-2)). Patients were divided in two groups: physically active (> 30 min/day of physical activity of at least moderate intensity, or TPA > moderate) and inactive (did not achieve these recommendations). The sample was also classified according to BMI (underweight, normal weight, overweight, and obese) and their %FM (moderate obesity, high obesity, and morbid obesity).In the whole group, TPA > moderate correlated weakly with BMI (r = -0.28; p = 0.02) and FM (r = -0.30; p = 0.001) but not with fat-free mass (FFM) (r = -0.18; p = 0.13). Physically inactive patients had higher body weight (p = 0.002), FM (p = 0.0005), and lower FFM as % of body weight (p = 0.03) than active patients. Obese patients (according to BMI) had a worse PADL level than underweight and normal-weight patients (p < 0.0001). A poorer PADL level occurred in morbidly obese patients (p = 0.01) despite the weak correlation between FM and TPA > moderate in the whole group.Physically active patients with COPD have proportionally more FFM and less FM than inactive patients. More pronounced physical inactivity occurs in obese patients, although body composition does not qualify as an important correlate factor of the level of PADL in patients with COPD.
Keywords: Chronic obstructive pulmonary disease; Obesity; Body mass index; Body composition; Exercise; Physical activity